1981
DOI: 10.1080/00071688108447866
|View full text |Cite
|
Sign up to set email alerts
|

Composition and amino acid content of carcass, skin and feathers of the growing gosling

Abstract: 1. Growth rate, food intake and utilisation were determined for goslings (Anser cireneus) from hatching to 7 weeks of age. 2. The relative weight of the carcass (body without feathers, skin or intestinal content) decreased from 0.83 of total body weight at hatching to 0.73 at 7 weeks. The skin relative weight increased from 0.12 at hatching to 0.17 at 2 weeks of age and subsequently remained constant. The weight of feathers increased from 0.034 of body weight at hatching to 0.08 at 7 weeks. 3. The fat of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…This may be attributed to a greater proportion of feathers in the laying-type birds in the first weeks of life. As compared to feather-free whole body protein, feather protein is characterized by a high concentration of cysteine (Nitsan et al, 1981;Stilborn et al, 1997). Due to the smaller body size of SG compared to FG genotype, feather protein contributes more to the whole body in laying-type chickens than in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to a greater proportion of feathers in the laying-type birds in the first weeks of life. As compared to feather-free whole body protein, feather protein is characterized by a high concentration of cysteine (Nitsan et al, 1981;Stilborn et al, 1997). Due to the smaller body size of SG compared to FG genotype, feather protein contributes more to the whole body in laying-type chickens than in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the goose to consume large quantities of feed may make it an interesting model in using forage material for the production of edible carcass protein. (March 1987) feathers as well as body fat (Nitsan and Nir 1977;Nitsan et al 1981;Fortin et al 1983;Stevenson 1985). Several studies have investigated the protein and/or amino acid report of Hollister et al (1984) in which diets varying in calorie:protein ratios were fed, it appears that dietary protein has not been a limiting factor in most goose feeding trials.…”
mentioning
confidence: 99%
“…Much of the fat content of the breast meat would come from the skin which, in the goose, makes up a relatively high portion of the breast weight (Nitsan et al 1981). …”
mentioning
confidence: 99%
“…The amino acids Pro, Lys, His and Cys were specifically affected by feather changes, and changes in connective tissues and muscles and their proportions in the body. In contrast, Nitsan et al (1981) who studied the AA composition of the body, skin and feathers of goslings from hatching to Day 42 of age, did not notice any effect of age. They found that gosling feather proteins are characterised by higher levels of Cys, Ser, Pro, Val and Tyr compared to the body and skin proteins.…”
Section: Dynamics Of Changes In Aa Levels In Chicken Dry Body Mattermentioning
confidence: 73%